Primary Hydatid Cyst of the Scaphoid: Case Report - Bulut, Mehmet; Tosun, H. Bayram; Simsek, Bengu Cobanoglu; Karakurt, Lokman (W B Saunders Co-Elsevier Inc, 2012)
Hydatid cyst caused by Echinococcus granulosus is a parasitic disease that can affect different organs. It is difficult to diagnose and has a tendency to recur. Primary bone involvement occurs in 0.5% to 4.0% of all patients with hydatid cysts. We present a 31-year-old woman with a primary hydatid cyst in the left scaphoid. Despite the availability of advanced imaging and laboratory investigation modalities (such as magnetic resonance imaging and serological studies) to make an adequate differential diagnosis of a cystic lesion in our case, intraoperative clinical suspicion led to the diagnosis. This was followed by a successful outcome without recurrence after 12 months. (J Hand Surg 2012;37A: 1051-1053. Copyright (C) 2012 by the American Society for Surgery of the Hand. All rights reserved.)
Keywords: Hydatid cyst; scaphoid; E granulosus; surgical treatment